Political Contestation in the Shadow of Hierarchy - Niclas Meyer (London School of Economics and Political Science (LSE), European Institute, 2012)
In the public policy literature, there is a widespread belief that industry self-regulation would only take place—and lead to satisfactory results—if industry was faced with a credible threat of hierarchical government intervention. At the example of intermodal transport standardization, however, this paper demonstrates that this does not have to be the case. It may even have a counterproductive effect by exposing self-regulatory processes to political contestation.
Keywords: 330; Shadow of hierarchy; self-regulation; private governance; technical standardization